Математическая модель и метод решения задачи упаковки интервальных параллелепипедов - Евсеева, Л. Г. (Видавничий дім "Академперіодика" НАН України, 2008)
A mathematical interval model of the problem of optimization of a packing of interval parallelepipeds is developed. The transition to a two-criterion problem in the Euclid space is realized. A strategy of the solution based on the use of both the optimization with respect to the groups of variables and the modified method of reducing neighborhoods is proposed.